Man 4 Jakarta Students' Perceptions on Online, Face-to-face, and Limited Face-to-face Learning During the Pandemic - Mohammad Izdiyan Muttaqin (EL-TARBAWI, 2022)
Indonesian government has been compelled to establish various learning approaches during this pandemic due to the spread of Covid-19 and the rising number of new cases, including distance learning and limited face-to-face learning. This study explores students' opinions about online learning, limited face-to-face learning, and face-to-face learning. The research was conducted at MAN 4 Jakarta. This study is situated in the mixed method. Data triangulation was carried out through field observations, surveys with 139 respondents, and structured interviews with 8 students. The survey results show that 47.5% of students prefer limited face-to-face learning with 1 day of face-to-face learning and 4 days of online meetings in one week. 38.1% of students prefer face-to-face learning, and 14.4% prefer online learning. The interviews suggest that students prefer face-to-face learning and limited face-to-face learning due to problems with internet connection. Offline and hybrid learning allow students to communicate with teachers easier. It offers an environment scaffolding learning enthusiasm. While some students choose online learning since it is less expensive and requires less time and effort to attend class, face-to-face learning is the most preferred by students.